Wild Helianthus species: A reservoir of resistance genes for sustainable pyramidal resistance to broomrape in sunflower - Chabaud, Mireille; Auriac, Marie-Christine; Boniface, Marie-Claude; Delgrange, Sabine; Folletti, Tifaine; Jardinaud, Marie-Françoise; Legendre, Alexandra; Pérez-Vich, Begoña; Pouvreau, Jean-Bernard; Velasco, Leonardo; Delavault, Philippe; Muños, Stéphane (Frontiers in Plant Science, 2022)
Orobanche cumana Wall., sunflower broomrape, is one of the major pests for the sunflower crop. Breeding for resistant varieties in sunflower has been the most efficient method to control this parasitic weed. However, more virulent broomrape populations continuously emerge by overcoming genetic resistance. It is thus essential to identify new broomrape resistances acting at various stages of the interaction and combine them to improve resistance durability. In this study, 71 wild sunflowers and wild relatives accessions from 16 Helianthus species were screened in pots for their resistance to broomrape at the late emergence stage. From this initial screen, 18 accessions from 9 species showing resistance, were phenotyped at early stages of the interaction: the induction of broomrape seed germination by sunflower root exudates, the attachment to the host root and the development of tubercles in rhizotron assays. We showed that wild Helianthus accessions are an important source of resistance to the most virulent broomrape races, affecting various stages of the interaction: the inability to induce broomrape seed germination, the development of incompatible attachments or necrotic tubercles, and the arrest of emerged structure growth. Cytological studies of incompatible attachments showed that several cellular mechanisms were shared among resistant Helianthus species.